Система муніципального права та її структурні елементи - Колобиліна, О. О.; Kolobylina, O. O.; Кобко, Р. В.; Kobko, R. V. (Вісник Луганського держаного університету внутрішніх справ ім. Е. О. Дідоренка. – 2023. - № 3(103). - С. 87-94, 2023)
Наголошено, що муніципальне право являє собою галузь права, система норм і принципів якої спрямована на регулювання суспільних відносин, які виникають у сфері діяльності місцевого самоврядування та управління муніципальними утвореннями, такими як міста, селища та сільські ради. Саме нормами цієї галузі права визначаються повноваження органів місцевого самоврядування, порядок їх формування та діяльності, а також права та обов'язки громадян відносно муніципальних утворень. Водночас предмет правового регулювання муніципального права окреслено як суспільні відносини в сфері реалізації територіальною громадою права на місцеве самоврядування, пов'язаного з вирішенням питань місцевого значення. З’ясовано сутність поняття «система муніципального права», надано характеристику ключовим елементам системи муніципального права.

It was established that municipal law is a branch of law, the system of norms and principles of which is aimed at regulating social relations that arise in the field of local selfgovernment and management of municipal entities, such as cities, towns, and village councils. It is the norms of this branch of law that determine the powers of local self-government bodies, the order of their formation and activity, as well as the rights and obligations of citizens in relation to municipal entities. It is noted that the public-law nature of this branch of law implies a close connection of municipal law with administrative and constitutional law. After all, local self-government bodies closely interact with state authorities in the course of their activities to address the needs of a specific community. At the same time, it was emphasized that the understanding of municipal law as an independent branch of law is a key aspect in the promotion of European integration processes, because the European community puts forward to Ukraine one of the basic conditions for building an effective and independent system of local self-government bodies. It is argued that the system of municipal law is a combination of municipal legal norms and institutions, which are located in a certain sequence and hierarchy depending on their importance and role in the regulatory and legal regulation of municipal relations. Given the definition proposed above, the key structural elements of the system of municipal law are: municipal legal norms and institutions. An approach is proposed, according to which the legal culture is understood as the primary element of the legal system in view of its system-forming, end-to-end character in relation to both the principles of law and the norms of law. It was noted that municipal law in today's conditions is an extremely important branch of law, the effectiveness of which depends on: first, the effectiveness of the completion of the municipal reform; secondly, the work of local self-government bodies, and therefore the implementation of state policy in the relevant sphere. That is why an important task of the legislator is to create the necessary conditions for the uninterrupted and high-quality functioning of all institutions of municipal law.

Отмечено, что муниципальное право представляет собой отрасль права, система норм и принципов которой направлена ​​на регулирование общественных отношений, возникающих в сфере деятельности местного самоуправления и управления муниципальными образованиями, такими как города, деревни и сельские советы. Именно нормами этой отрасли права определяются полномочия органов местного самоуправления, порядок их формирования и деятельности, а также права и обязанности граждан в отношении муниципальных образований. В то же время, предмет правового регулирования муниципального права очерчен как общественные отношения в сфере реализации территориальной общиной права на местное самоуправление, связанного с решением вопросов местного значения. Выяснена сущность понятия «система муниципального права», дана характеристика ключевым элементам системы муниципального права.
System of municipal law and its structural elements
Keywords: муніципальне право; місцеве самоврядування; система права; інститут права; municipal law; local self-government; legal system; legal institute; муниципальное право; местное самоуправление; институт права